1987
DOI: 10.1097/00132586-198712000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Inflation Pressure, Gastric Insufflation and Rapid Sequence Induction

Abstract: Manual inflation of the lungs should be avoided (before tracheal intubation) when rapid sequence induction is performed. This teaching is applied to all patients at risk from the dangers of a full stomach, particularly in obstetric practice. Unless hypoxia supervenes, manual ventilation is contraindicated on two grounds. First, if cricoid pressure has been inadequately applied (a not uncommon situation (Howells et al., 1983)), silent regurgitation may occur and gastric contents be forced into the lungs. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 0 publications
0
40
0
4
Order By: Relevance
“…However, the time to desaturation following pre-oxygenation is shorter in apneic infants compared to older children (<100 s), and a modified RSI technique with gentle pressure-limited mask ventilation (10-12 cm H2O) and 100 % oxygen may be used to avoid hypoxemia [119,120]. This technique may also limit hypercarbia and keep small airways open without the risk of gastric inflation and related morbidity [121][122][123]. Cricoid pressure is routinely applied despite questionable evidence that it improves clinical outcomes [123][124][125].…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…However, the time to desaturation following pre-oxygenation is shorter in apneic infants compared to older children (<100 s), and a modified RSI technique with gentle pressure-limited mask ventilation (10-12 cm H2O) and 100 % oxygen may be used to avoid hypoxemia [119,120]. This technique may also limit hypercarbia and keep small airways open without the risk of gastric inflation and related morbidity [121][122][123]. Cricoid pressure is routinely applied despite questionable evidence that it improves clinical outcomes [123][124][125].…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…However, the original studies that demonstrated these findings used much higher tidal volumes than those currently recommended. 66,67 More recent data now show that cricoid pressure hampers the placement of both supraglottic and endotracheal airways. Cricoid pressure impairs both laryngeal mask airway placement and subsequent ventilation.…”
Section: Airway Adjunctsmentioning
confidence: 99%
“…60 This report, however, differs from the results of two studies (a cadaver study and a clinical study) that documented decreased gastric insufflation with air during mask ventilation when cricoid pressure was applied. 61,62 This raises the question or whether or not studies with mask ventilation can be applied to endotracheal intubation and what effect, if any, cricoid pressure has on preventing gastric aspiration during endotracheal intubation. A literature review of 241 articles dealing with cricoid pressure concluded there was little evidence to support the view that cricoid pressure decreases the risk for aspiration.…”
Section: Step 3: Pretreatmentmentioning
confidence: 99%